Answer:
5. Y = -3X -2
7. K = (DW -GRP)/L
9. T = J + L - T
10. B = DF - A - C
Explanation:
In each case, the steps are the same:
- Subtract every term that does not contain the variable of interest.
- Divide by the coefficient of the variable of interest.
- Simplify as needed.
___
5. The variable of interest (Y) is on the left side of the equation. The other term there is -3X, so we add 3X (same as subtract -3X) to both sides of the equation:
-4Y = 12X + 8
Now, we divide both sides by -4.
Y = -3X -2
7. The term not containing K on the left side of the equation is DW/G, so we subtract that from both sides of the equation.
-KL/G = RP -DW/G
Now, we multiply the equation by the inverse of the coefficient of K, which is -G/L:
K = (-G/L)·RP -(-G/L)·(DW/G) = -GRP/L +DW/L
K = (DW -GRP)/L
+++
In this case, it can be a little easier if you multiply by G first, then subtract DW and divide by -L. The end point is the same, but the route is slightly different.
9. Terms not containing T are P and -L. Subtracting those from both sides of the equation gives ...
T = J +L -T
10. Subtracting terms A and C from both sides of the equation gives ...
B = DF -A -C